Investigation into the biocompatibility and antibacterial performance of TiO2 silicone nanocomposites - James Quinn; Eugénie Guimier; Louise Carson; Karl Malcolm (University of Huddersfield Press, 2022)
Incorporation of nanoparticles into silicone elastomers to form silicone nanocomposites is an area of ongoing research, with a broad range of biomedical applications. Addition-cure silicone nanocomposite dispersions were prepared, containing TiO2 of varying nanoparticle sizes and concentrations. All TiO2 silicone nanocomposites remained biocompatible (cell viability >70% relative to control silicone) when assessed via direct contact MTT assay. However, results from bacterial adherence studies demonstrated that 1000 nm and 200 nm TiO2 nanocomposites displayed a greater antibacterial effect in comparison to 100 nm and 20 nm TiO2nanocomposites. The data suggests TiO2 silicone nanocomposites possess antibacterial properties (that is dependent on particle size) and are cytocompatible, warranting further research into potential uses for biomedical applications.